2016
DOI: 10.1007/s13738-016-0923-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired synthesis, characterization and antifungal activity of enzyme-mediated gold nanoparticles using a fungal oxidoreductase

Abstract: by disk diffusion method indicated a potent growth inhibitory activity against all tested human pathogenic yeasts and molds by inhibition zones ranged from 10 to 18 mm. Taken together, our enzymatically established method of nanoparticle synthesis using a purified sulfite oxidoreductase of F. oxysporum can be considered as an efficient tool for generating harmless bioactive gold nanoparticles with potential applications in biology, medicine and industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“… Nanoparticles Fabrication method Fungal growth (mm) Ref. Au Nps Green synthesis 8.66 62 Au Nps Green synthesis 14.2 63 Au Nps Green synthesis 10 64 Au Nps Green synthesis 12 65 AuS1, AuS2, and AuS3 Green synthesis 42.33, 47.33, and 42.33 Present work …”
Section: Resultsmentioning
confidence: 99%
“… Nanoparticles Fabrication method Fungal growth (mm) Ref. Au Nps Green synthesis 8.66 62 Au Nps Green synthesis 14.2 63 Au Nps Green synthesis 10 64 Au Nps Green synthesis 12 65 AuS1, AuS2, and AuS3 Green synthesis 42.33, 47.33, and 42.33 Present work …”
Section: Resultsmentioning
confidence: 99%
“…The obtained NPs were spherical in shape with an average size of 20 nm as determined by SEM, TEM and DLS. NPs showed very high growth inhibitory activity against all tested human pathogenic yeasts and molds [98].…”
Section: 8mentioning
confidence: 99%
“…They reported that all conjugated triangular NPs and naked triangular AuNPs showed enhanced antifungal properties; however, this property was not observed with any peptide ligands. In another study, Gholami-Shabani et al ( Gholami-Shabani et al, 2016 ) developed a cell-free system to generate AuNPs by using purified sulfite oxidoreductase (a fungal oxidoreductase) of Fusarium oxysporum ( F. oxysporum ). These researchers used the disk diffusion method to assess the antifungal activities of prepared NPs.…”
Section: Metallic-nanoparticle-based Antifungal Therapeutic Strategiesmentioning
confidence: 99%
“…They observed strong growth inhibitory properties against all tested human pathogenic molds and yeasts, as demonstrated by inhibition zones ranging from 10 to 18 mm ( Gholami-Shabani et al, 2016 ). Collectively, it was indicated that the preparation of NPs by using a purified sulfite oxidoreductase of F. oxysporum can be effective in producing safe bioactive AuNPs, which can be effectively used in the field of medicine ( Gholami-Shabani et al, 2016 ). In Table 2 , a summary of the antifungal potentials of various MNPs and metal oxide NPs has been provided.…”
Section: Metallic-nanoparticle-based Antifungal Therapeutic Strategiesmentioning
confidence: 99%